qPCRtools: An R package for qPCR data processing and visualization - Li, Xiang; Wang, Yingmin; Li, Jingyu; Mei, Xinyue; Liu, Yixiang; Huang, Huichuan (Frontiers in Genetics, 2022)
In biological research, qPCR is a technique that is frequently used to measure gene expression levels. The calculation of gene amplification efficiency is a critical step in the processing of qPCR data since it helps to decide which method to employ to compute gene expression levels. Here, we introduce the R package qPCRtools, which enables users to analyze the efficiency of gene amplification. Additionally, this software can determine gene expression levels using one of three approaches: the conventional curve-based method, the 2-ΔΔCt method, and the SATQPCR method. The qPCRtools package produces a table with the statistical data of each method as well as a figure with a box or bar plot illustrating the results. The R package qPCRtools is freely available at CRAN (https://cran.r-project.org/web/packages/qPCRtools/index.html) or GitHub (https://github.com/lixiang117423/qPCRtools/tree/main/CRAN/qPCRtools).